Designing a Self-cleaning Table and Alcohol Spraying On the Table Automatically in Fast Food Restaurants to Prevent the Spread of Coronavirus - Majid Sokoot Jahromia, Farzaneh Goli, Hamed Pourmohammadi Emamiyeh , Vahid Noei (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Smart restaurants are being developed today. As an integral part of the restaurant system, designing the table is bound to face a qualitative leap. As people yearn for a better, more comfortable and convenient life, the development of the table in smart restaurants will become more intelligent and humanized. At present, people are in great demand for smart service and cleaning in restaurants, and they hope that the table will be completely clean after eating or before ordering food, and that no food debris will remain on the table. Especially in this period due to the spread of Corona virus while human interactions should be reduced, the lack of table cleaning is intelligently visible. currently, most restaurants and fast foods, whether smart or ordinary, use humans to clean up food waste, which increases the likelihood that restaurant staff will over-treat guests and customers. In this plan, the moving part (chariot) is mounted on the table, which automatically collects food waste and directs it to the trash can installed next to the table. The Arduino board is used in a closed-loop system to control the moving part and the trash can lid. The moving part of the table collects food waste along the way and disinfects the table on the way back to the original point through alcohol spraying.